Octopus a cruise to hell - Lerner, Danny; Davidson, Boaz ([United States] : Nu Image, 2000)
An elite nuclear submarine, on a deadly mission to deliver an international terrorist to American authorities, travels through a mysterious ocean portal known as'The Devil's Eye.' Twenty-seven ships have disappeared in this area, fueling the legend of a killer mutant octopus
Executive producer, Avi Lerner ; editor, Alain Jakubowicz ; screenplay, Michael Weiss ; story, Boaz Davidson
Cast: Jay Harrington, David Beecroft, Carolyn Lowery, Ricco Ross
VCD format
Keywords: Animal films; Animals in motion pictures; Suspense in motion pictures